Analysis of Differences of Serum Thromboxane B2 Level after Taking Acetosal in Acute Thrombotic Stroke with Diabetes Mellitus and Non-Diabetes Mellitus - Hadiyanti, Nur; Hasmono, Didik; Islam, Mohammad Saiful (Folia Medica Indonesiana, 2018)
Endothelial dysfunction and vascular injuries are the early processes in thrombogenesis leading to thrombotic stroke. These processes trigger platelet activation characterized by synthesis of Thromboxane A2, potent agonist in platelet aggregation. Acetosal (ASA) 100 mg usually given to thrombotic stroke patients exerts its pharmacological effect by inhibition of TxA2 synthesis, thus could prevent thrombus formation. Diabetes mellitus (DM) as risk factor of thrombotic stroke exhibits an increase in TxA2 synthesis. It is not known whether ASA 100 mg could inhibit TxA2 adequately in diabetic patients. This study aimed to analyze the differences of serum TxA2 level, which was measured by serum TxB2 level as stabile metabolite of TxA2, after taking ASA 100 mg in diabetic and non-diabetic thrombotic stroke patients. This prospective observational study was held in Neurology Department of Dr. Soetomo Hospital, Surabaya. Total 27 patients, consisted of 15 patients with DM and 12 patients with non-DM were enrolled. Serum TxB2 was measured before and after 5-7 days 100 mg ASA 100 administration. Mean value of serum TxB2 level before and after taking ASA was 16.43 ± 16.08 ng/mL and 2.93 ± 1.83 ng/mL in diabetic and 27.36 ± 21.04 ng/mL and 5.36 ± 4.06 ng/mL in non-diabetic group. Mean reduction of serum TxB2 level in diabetic and non-diabetic group was 13.49 ± 15.9 ng/mL and 22.00 ± 21.65 ng/mL. There were significant differences in serum TxB2 level after taking ASA 100 mg in diabetic and non-diabetic group but the mean reduction of serum TxB2 level were not significantly different.